Evaluation and clinical impact of a pharmacist-led, interdisciplinary service focusing on education, monitoring and toxicity management of immune checkpoint inhibitors. (January 2023) - Myers, Glenn; Stevens, Jonathan; Flewelling, Andrew; Richard, Jacqueline; London, Meagan
Introduction: Immune-related adverse events are complications of immune checkpoint inhibitors which require robust patient education and proactive follow-up to ensure timely identification and management. Oncology pharmacist practice models with other anticancer modalities have been well documented, but there is limited evidence assessing the spectrum of pharmacist interventions in patients receiving immune checkpoint inhibitor(s) and the impact of these interventions on patient outcomes. Methods: Patients initiated on immune checkpoint inhibitor(s) from 1 January 2016 to 31 August 2019 were included for data collection and analysis. Part 1 featured an intensive pharmacist follow-up cohort (study cohort) and summarized pharmacist interventions. Part 2 compared patient outcomes between the study cohort and a standard of care cohort (control cohort) from a different oncology centre. Patient outcomes included emergency department visits not resulting in admission, hospitalizations due to immune-related adverse event(s), immune checkpoint inhibitor cycles received, treatment discontinuation due to immune-related adverse event(s), completion of finite programmed death-1/death-1 ligand treatment course and completion of ipilimumab. Clinical outcomes were compared using a retrospective, matched cohort design based on age, cancer diagnosis and immune checkpoint inhibitor(s). Results: A total of 143 patients were included in Part 1 encompassing 1664 pharmacist recommendations across 11 categories. The matched cohort yielded 92 matches (n = 184) with a higher odds of immune checkpoint inhibitor discontinuation due to immune-related adverse event(s) in the control cohort (odds ratio (OR) (95% confidence interval (CI)) = 5.5 (1.2−24.8); p  = 0.022). Conclusion: Intensive immune-related adverse event education, proactive follow-up and immune-related adverse event management by pharmacists result in clinically meaningful interventions which correlate to improved patient outcomes, namely lower odds of treatment discontinuation due to immune-related adverse event(s).